Safety and effectiveness of endobiliary radiofrequency ablation according to the different power and target temperature in a swine model. Issue 2 (February 2017) - Cho, Jae Hee; Lee, Kwang Hyuck; Kim, Joon Mee; Kim, Yeon Suk; Lee, Don Haeng; Jeong, Seok
Abstract: Background and Aim: Endobiliary radiofrequency ablation (EB‐RFA) is a new endoscopic palliation and adjunctive tool. Although EB‐RFA is performed worldwide, a possibility of iatrogenic thermal injury leading to perforation or bleeding still remains. Therefore, we aimed to assess the effects of thermal and coagulation injury after in vivo EB‐RFA using a new catheter with a temperature sensor in a swine model. Methods: Twelve mini pigs were divided into four groups according to power (33 mm 10 W electrode vs. 18 mm 7 W electrode) and RFA target temperature (75°C vs. 80°C). All mini pigs underwent endoscopic retrograde cholangiography and target temperature controlled EB‐RFA for 120 s. Additional cholangiogram was taken immediately after RFA, and all pigs were sacrificed after 24 h to assess the macroscopic/microscopic RFA injury. Results: Microscopic maximal injury depth and ablation area of EB‐RFA using a 33‐mm 10 W RFA electrode were significantly deeper and larger than those of EB‐RFA using an 18‐mm 7 W electrode (median; 2.7 vs. 2.1 mm, P = 0.004, 48.9 vs. 36.2 mm 2, P = 0.016). However, there were no significant differences in microscopic ablation parameters between two different RFA target temperatures (75°C vs. 80°C). In addition, a post‐RFA cholangiogram and assessment of the resected specimen at 24 h after the RFA showed no adverse events such as perforation or bleeding. Conclusions: EB‐RFA using a temperature controlled RFA catheter successfully ablates the bile duct wall without adverse events in a swine model.